Childhood Neglect History, Depressive Symptoms, and Intimate Partner Violence Perpetration by College Students - Brennan, Carolyn L. (Journal of interpersonal violence, 2021)
College students experience intimate partner violence (IPV) at an alarming rate, and preventing such violence depends on identifying factors that contribute to perpetration. Although there is extensive research that has established a link between childhood neglect and later physical IPV perpetration, less is known about the specific mechanisms through which childhood neglect leads to IPV perpetration. In the present study, we examined potential mediators of the relationship between childhood neglect and IPV perpetration by college students, with special emphasis on the role of depressive symptoms and IPV victimization. A total of 302 college students reported on their experiences of childhood maltreatment, depressive symptoms, and IPV victimization and perpetration. Results indicate that increasing levels of childhood emotional and physical neglect correspond with increasing rates of IPV perpetration, after accounting for the effect of childhood emotional, physical, and sexual abuse. This effect between childhood neglect and IPV perpetration was fully mediated by the combination of IPV victimization and depressive symptoms for the overall sample. However, when examining the model for men and women separately, only the indirect effect through victimization remained statistically significant for men. Our findings suggest that research on the link between childhood neglect and IPV perpetration should also consider the impact of IPV victimization, as neglect may lead to IPV perpetration within the context of a mutually aggressive relationship. Furthermore, these findings indicate that childhood neglect leads to long-term emotional consequences that contribute to later IPV perpetration, and treating depressive symptoms may help prevent IPV perpetration against college students who experienced childhood neglect.